2016
DOI: 10.3390/su8100993
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Injection on the Control of In-Cylinder Pressure and Enhanced Power Output in a Four-Stroke Spark-Ignition Engine

Abstract: This paper presents the results for liquid water injection (WI) into a cylinder during the compression and expansion strokes of an internal combustion engine (ICE), with the aim of achieving an optimal in-cylinder pressure and improving power output using CFD simulation. Employing WI during the compression stroke at 80 • of crank angle (CA) before top dead centre (bTDC) resulted in the reduction of compression work due to a reduction in peak compression pressure by a margin of about 2%. The decreased peak comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…With increasing the water mass fraction to 15%, the quality of combustion decreases significantly, because the number of water and gasoline moles in this mass fraction, are almost equal, and since both of these materials, affect the combustion process equally, water absorbs some of the combustion heat and it decreases the combustion quality. According to Figures 15 and 7, it can be observed that in the mass fraction of 20%, the pressure rise is not due to the increase of combustion quality because the CO and CO2 emission levels are not significantly changed; thus as it was indicated before, this pressure rise can be due to the higher number of water moles in the combustion chamber [43].…”
Section: Resultsmentioning
confidence: 59%
“…With increasing the water mass fraction to 15%, the quality of combustion decreases significantly, because the number of water and gasoline moles in this mass fraction, are almost equal, and since both of these materials, affect the combustion process equally, water absorbs some of the combustion heat and it decreases the combustion quality. According to Figures 15 and 7, it can be observed that in the mass fraction of 20%, the pressure rise is not due to the increase of combustion quality because the CO and CO2 emission levels are not significantly changed; thus as it was indicated before, this pressure rise can be due to the higher number of water moles in the combustion chamber [43].…”
Section: Resultsmentioning
confidence: 59%
“…Water injection helped in reducing the energy losses resulting from the transfer of heat to the walls and exhaust gases [21]. So, Brown's Gas has 3 main functions, is: (1) Save fuel, and increase mileage per liter; (2) Minimize emissions which are the main cause of the greenhouse effect; and (3) Improve engine performance and strength.…”
Section: Figure-1mentioning
confidence: 99%
“…This is because less energy is required to compress the charge air. This advantage should be significant in high compression ratio engine due to the increase of in-cylinder pressure at the latter stage of compression stroke [15]. Besides the reduction of compression work, the reduced pressure also helps to reduce the suction gas losses result from blow-by past the piston rings [14].…”
Section: Effect Of Port Wi On the Combustion Temperature And In-cylinmentioning
confidence: 99%
“…There are some simulation works that are worth to be highlighted [3,4,7,[12][13][14][15]. Since this paper is related to numerical approach, only the prior studies which used numerical approach is highlighted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation